Testing of silicon rubber/montmorillonite nanocomposite for mechanical and tribological performance - Shinde, Avinash; Siva, I.; Munde, Yashwant; Deore, Vishal; Hameed Sultan, Mohamed Thariq; Md Shah, Ain Umaira; Mustapha, Faizal (MDPI AG, 2021)
Nanocomposite made by blending nano-montmorillonite (MMT) and Silicon Rubber (SR) for mechanical and tribological performance is explored in this work. Different configurations of MMT/SR nanocomposite, with 0, 0.5, 2 and 5 wt % of MMT are manufactured by two roll mixing methods. Noticeable improvement in the mechanical and tribological performance is observed, which is also justified by a morphological study of fractured and wear surfaces through SEM. Two percent of MMT loading is found to be the optimum content that shows excellent performance compared to other compositions. The performance improvement can be linked to the good interfacial interaction between the MMT and SR. Statistical modeling through ANOVA is carried out for tribological performance, which reveals the influence of load on the coefficient of friction (COF) and the influence of sliding distance on the wear rate.